Efficient synthesis of diospyrol via Suzuki-Miyaura and modified in situ cross-coupling - Poolsak Sahakitpichan (2018)
Tetramethoxydiospyrol was synthesized via Suzuki-Miyaura cross-coupling of the two key intermediates, halonaphthalene and naphthaleneboronic acid derivatives, which were derived from the same naphthol. Moreover, the product could be conveniently obtained by a one-pot modified in situ Suzuki coupling. The naphthol was synthesized via the cyclization of ortho-allylbenzamide intermediate. © Georg Thieme Verlag Stuttgart.